Onde usamos o mosaico? - Buriola, Ana Flávia Marçal; Bernhard , Cristiane Otília Colossi; Minotti, Fabielle Ferreira da Silva; Santos , Eliana Ferreira dos (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf